Application of DRASTIC Method for Groundwater Vulnerability Analysis to Contamination in Pemalang District, Pemalang Regency, Central Java Province, Indonesia - Firginawan Surya Wanda; Doni Prakasa Eka Putra; Wahyu Wilopo (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Pemalang District, Pemalang Regency, Central Java Province, as the district's capital, has experienced rapid economic and population growth. This has resulted in increased exploitation and degradation of groundwater quality, with groundwater extraction increasing from 91,856 m³ to 133,708 m³. There was an average decrease in groundwater levels of 40-70 cm from 2020 to 2023, and an increase in nitrate and chloride levels in groundwater was recorded from 2021 to 2023. To maintain the availability of groundwater that is suitable for use, efforts are needed to prevent groundwater contamination in vulnerable areas. The approach applied to examine groundwater vulnerability to contamination is the DRASTIC method. The research location is a coastal area composed of quaternary deposits with lithology consisting of sand and gravel in the south and clay and silt in the north. It has a shallow groundwater depth and a groundwater flow pattern that flows from south to north. The results of the geospatial analysis revealed two zones of groundwater vulnerability to contamination, based on the DRASTIC Index value, consisting of moderate vulnerability   (>106-146) and high vulnerability (>146-186). There were 67.4% of high vulnerability zones in this research area, spread from the central part, which is Wanamulya Village, to the southern part, which is Surajaya Village.